The Semiotics Analysis on the Environment in “The Journey to Atlantis” Picture Book - Darsita Suparno; Laksmy Ady Kusumoriny (Lexeme : Journal of Linguistics and Applied Linguistics, 2020)
This study aimed (1) to describe the semiotic process of environment symbols in The Journey to Atlantis, (2)to generate the meaning of identified symbols which are shown through verbal and non-verbal contained in The Journey to Atlantis. This is a descriptive qualitative study trying to identify and analyze semiosis process of environment symbols, and describe the found verbal and nonverbal symbols in Elisabetta Dami’s The Journey to Atlantis Picture Book using semiotic theory by Charles Sanders Peirce (1991).  The data for the finding and analysis were taken from Elisabetta Dami’sThe Journey to Atlantis (2012) Picture Book. The study shows that there are 40 icons in form of words and 36 onomatopoeia as verbal symbols, and 40 picture decribe Atlantis environment and 18 color as nonverbal symbols which are related to the environment.